Evaluation of lorcaserin on progression of prediabetes to type 2 diabetes and reversion to euglycemia. Issue 4 (18th May 2016) - Nesto, Richard; Fain, Randi; Li, Yuhan; Shanahan, William
ABSTRACT: Objectives : Lorcaserin is a selective 5-HT2C (5-hydroxytryptamine 2C) receptor agonist indicated for weight management. Here, we assess the impact of lorcaserin on progression from prediabetes to type 2 diabetes (T2D) and on reversion from prediabetes to euglycemia. Methods : This is a post hoc analysis of pooled data from two Phase 3 studies, BLOOM and BLOSSOM (N = 6136), evaluating the impact of lorcaserin on weight and glycemic parameters over 52 weeks in the subpopulation of obese/overweight subjects with prediabetes, alternately defined by fasting plasma glucose (FPG) 100–125 mg/dl or glycated hemoglobin (HbA1c) 5.7–6.4% at baseline. Results : At Week 52, in the subpopulation with prediabetes, nearly twice as many lorcaserin-treated subjects achieved ≥5% weight loss versus placebo (HbA1c: 55.6% vs. 27.5%, p < 0.001; FPG: 52.8% vs. 28.8%, p < 0.001), and a significantly lower percentage of lorcaserin-treated subjects progressed to T2D versus placebo based on HbA1c (lorcaserin 3.2%, placebo 5.0%, p = 0.032) but not FPG (lorcaserin 1.6%, placebo 2.6%, p = 0.227). A significantly greater proportion of lorcaserin-treated subjects versus placebo also reverted to euglycemia based on both HbA1c (lorcaserin 40%, placebo 29.5%, p < 0.001) and FPG (lorcaserin 52.4%, placebo 46.5%, p = 0.047). Conclusion : In subjects with prediabetes, lorcaserin may contribute to weight loss and improve glycemic parameters, and thus may help with preventing progression to T2D and promoting reversion to euglycemia. Clinical trial registration :www.clinicaltrials.gov identifiers are NCT00395135 (BLOOM) and NCT00603902 (BLOSSOM)